ANTIDIARRHOEAL ACTIVITY OF AN ETHANOL EXTRACT OF THE STEM BARK OF PILIOSTIGMA RETICULATUM (CAESALPINIACEAE) IN RATS - DOSSO, Kassim; N’guessan, B B; Bidie, A P; Gnangoran, B N; Méité, S; N’guessan, D; Yapo, A P; Ehile, E E (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Piliostigma reticulatum (Caesalpiniaceae) is used in Africa as a traditional medicine for the treatment of many diseases, such as malaria, tuberculosis and diarrhoea. We investigated the antidiarrhoeal properties of a crude ethanol extract from the stem bark of Piliostigma reticulatum (EEPR) in Wistar albino rats to substantiate its traditional use and to determine its phytochemical constituents. The antidiarrhoeal activity of the plant extract was evaluated in a castor oil-induced diarrhoea model in rats and compared with loperamide. The effect of the extract on gastrointestinal motility was also determined by the oral administration of charcoal meal and castor oil-induced intestinal fluid accumulation (enteropooling). EEPR showed remarkable dose-dependent antidiarrhoeal activity evidenced by a reduction of defecation frequency and change in consistency. Extracts at 250, 500 and 1000 mg/kg body weight significantly reduced diarrhoeal faeces. EEPR also significantly inhibited gastrointestinal motility and castor oil-induced enteropooling at 500 and 1000 mg/kg, similar to the inhibition obtained in control rats treated by atropine. Phytochemical screening revealed the presence of tannins, flavonoids, polyphenols and reducing sugars in the stem bark of P. reticulatum. No mortality or visible signs of general weakness were observed in the rats following administration of the crude extract in doses up to 6000 mg/kg body weight in an acute toxicity study. Our results show that the stem bark of P. reticulatum possesses antidiarrhoeal activity and strongly suggest that its use in traditional medicine practice could be justified.